Desarrollo hardware de un Procesador Difuso Tipo Dos - Melgarejo Rey, Miguel Alberto; Peña Reyes, Carlos A. (Ingeniería, 2003)
This paper presents an architectural proposal for a hardware-based interval type-2 fuzzy inference system. First, it presents a computational model which considers parallel inference processing. Taking into account this model, we conceived a hardware architecture with several pipeline stages for full parallel execution of type-2 fuzzy inference. The architectural proposal is used for specifying a type-2 fuzzy processor, which is implemented over FPGA technology. Implementation results show this processor performs more than 30 millions of type-2 fuzzy inferences per second. As target application, it is used to implement two fuzzy adaptive filters.